2013
DOI: 10.1049/iet-epa.2012.0206
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal periodic carrier frequency modulation in reducing electromagnetic noise of permanent magnet synchronous motor

Abstract: This study introduces a simple method to reduce the electromagnetic noise of permanent magnet synchronous motor (PMSM) fed by pulse-width modulation (PWM) inverter. The analysed relationship between PMSM electromagnetic noise and current harmonic shows that PMSM electromagnetic noise concentrating on integral multiples of switching frequency is produced by the concentrative current harmonic. To spread the current harmonic spectrum, sinusoidal periodic carrier frequency modulation (PCFM) is presented and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Considering the actual control environment, in which the motor windings are connected to the inverter and excited by the voltage source, the space vector pulse width modulation (SVPWM) technique is thus employed among various modulation techniques, due to its superior performance in bus voltage utilization and overall efficiency [8][9][10]. Current harmonics generated by pulse width modulation (PWM) cannot be ignored when using an SVPWM control strategy because it leads to the increase of the losses, torque ripple, vibration, and noises [11][12][13][14][15][16][17]. In particular, in [11,12], it is shown that the eddy-current loss of the magnets increases significantly, caused by high-order carrier harmonics of the inverter, bringing the risk of irreversible demagnetization of the magnets.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the actual control environment, in which the motor windings are connected to the inverter and excited by the voltage source, the space vector pulse width modulation (SVPWM) technique is thus employed among various modulation techniques, due to its superior performance in bus voltage utilization and overall efficiency [8][9][10]. Current harmonics generated by pulse width modulation (PWM) cannot be ignored when using an SVPWM control strategy because it leads to the increase of the losses, torque ripple, vibration, and noises [11][12][13][14][15][16][17]. In particular, in [11,12], it is shown that the eddy-current loss of the magnets increases significantly, caused by high-order carrier harmonics of the inverter, bringing the risk of irreversible demagnetization of the magnets.…”
Section: Introductionmentioning
confidence: 99%
“…Power converters for electrical energy conversion have been widely used in the renewable energy applications such as motor control, electric vehicle, energy storage, high-power-factor rectifiers, and compensators for reactive and harmonic currents to the grid [5][6][7][8][9][10][11][12][13][14][15]. In these systems, at least two current sensors are employed to implement the closed-loop current control and overcurrent protection.…”
Section: Introductionmentioning
confidence: 99%
“…. , 7 ) for further analysis. First of all, the proposed phase current reconstruction method in this paper is available when the currents are sampled during the ZVVs.…”
Section: Introductionmentioning
confidence: 99%
“…In case of constant-frequency PWM, these noise components are concentrated in narrow bands around integral multiples of the carrier frequency, which is irritating to the human ear [14]. Hence numerous variable-frequency or random-frequency PWM methods have been proposed which ensure that the acoustic noise is spread over a wide range of frequencies [15]- [17]. However, these methods might not lead to reduction in the overall noise emitted; the total harmonic distortion (THD) in the line current could also be increased [18], [19].…”
Section: Introductionmentioning
confidence: 99%